Patient Experience with Postpartum Pain Management in the Face of the Opioid Crisis. (4th March 2021) - Leziak, Karolina; Yee, Lynn M.; Grobman, William A.; Badreldin, Nevert
Abstract : Introduction: Professional societies have urged providers to reduce opioid use for pain management. Accordingly, the objective of this study was to assess patient experiences related to postpartum pain management in an effort to better understand potential paths to achieve such a reduction. Methods: This is a planned secondary analysis of a prospective observational study of opioid use following birth. In the primary study, women who received opioids as inpatients were queried about their pain management, including questions about pain experience, pain satisfaction, perceived areas for practice improvement, and the opportunity to leave additional comments. Participants who were prescribed opioids upon discharge completed postdischarge surveys with a similar opportunity for qualitative input. Data were analyzed using the constant comparative method to identify themes and subthemes. Results: Of the 493 women enrolled in the primary analysis, 125 provided qualitative data. Three overarching themes regarding pain management were identified: positive experiences (n = 22), negative experiences (n = 19), and beliefs and preferences on opioid use and pain management (n = 28). Women with positive experiences reported satisfaction with timely pain medication administration and appreciation of open dialogue with their care team. In contrast, several negative experiences centered on tardy administration of pain medications, resulting in increased pain. Patients also perceived judgment, accusation, and excessive lecturing by staff when requesting opioid medications. Finally, participants expressed the necessity for opioids for postpartum pain management, as well as their desires for limiting opioid use, improved options for multimodal pain management, and increased communication with providers about pain regimens. Discussion: Understanding women's perspectives and experiences regarding postpartum pain control is essential to improving care. Amid growing research on the role of maternity care providers in addressing the opioid crisis, women's voices are rarely solicited. These findings stress the importance of open and frequent dialogue between patients and providers and a need for multimodal pain management options.